Pengaruh Kepemilikan Asing, Ukuran Perusahaan, dan Pertumbuhan Perusahaan Terhadap Pengungkapan Corporate Social Responsibility - Rani Dwicahyati; Ita Darsita (CV. ITTC INDONESIA, 2025)
This study aims to examine the influence of foreign ownership, firm size, and firm growth on Corporate Social Responsibility (CSR) disclosure in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The population consists of 130 companies, with 8 selected as samples using purposive sampling. Covering a five-year span, a total of 40 observational data points were analyzed. This research employs a quantitative approach with panel data regression analysis. The type of data used is secondary data, sourced from annual reports and sustainability reports. CSR disclosure levels are measured based on the Global Reporting Initiative (GRI) 2016 indicators. The results show that partially, firm size has a significant effect on CSR disclosure. Meanwhile, foreign ownership and firm growth have no significant effect. However, when tested simultaneously, all three variables collectively influence the level of CSR disclosure.